Minimization of Surface Roughness and Tool Vibration in CNC Milling Operation. (31st January 2015) - Bhogal, Sukhdev S.; Sindhu, Charanjeet; Dhami, Sukhdeep S.; Pabla, B. S.
Abstract : Tool vibration and surface roughness are two important parameters which affect the quality of the component and tool life which indirectly affect the component cost. In this paper, the effect of cutting parameters on tool vibration, and surface roughness has been investigated during end milling of EN-31 tool steel. Response surface methodology (RSM) has been used to develop mathematical model for predicting surface finish, tool vibration and tool wear with different combinations of cutting parameters. The experimental results show that feed rate is the most dominating parameter affecting surface finish, whereas cutting speed is the major factor effecting tool vibration. The results of mathematical model are in agreement with experimental investigations done to validate the mathematical model.